Fischer–tropsch diesel production and evaluation as alternative automotive fuel in pilot-scale integrated biomass-to-liquid process. (15th October 2016) - Kim, Young-Doo; Yang, Chang-Won; Kim, Beom-Jong; Moon, Ji-Hong; Jeong, Jae-Yong; Jeong, Soo-Hwa; Lee, See-Hoon; Kim, Jae-Ho; Seo, Myung-Won; Lee, Sang-Bong; Kim, Jae-Kon; Lee, Uen-Do
Highlights: A pilot scale biomass-to-liquid (BTL) process was investigated for Fischer-Tropsch diesel production. 200 kWth dual fluidized bed gasifier was integrated with 1 bbl/day F-T synthesis reactor. Purified syngas satisfies minimum requirements of F-T synthesis. F-T diesel produced successfully (1 L/h) and satisfies the automotive fuel standard. Fully integrated BTL system was operated successfully more than 500 h. Abstract: Fischer–Tropsch (F-T) diesel produced from biomass through gasification is a promising alternative fuel. In this study, a biomass-to-liquid (BTL) system involving a dual fluidized bed gasifier (DFBG), a methanol absorption tower, and an F-T synthesis process was investigated for producing clean biodiesel as an automotive fuel. A DFBG, which is an efficient indirect gasifier, can produce syngas with high caloric value while minimizing the amount of nitrogen in the product gas. In order to meet the strict requirements of syngas for F-T synthesis, any contaminants in the syngas must be minimized and its composition must be carefully controlled. In this work, the syngas mainly comprised 35 vol% of H2 and 21.3 vol% of CO. The concentrations of H2 S and COS in the syngas were less than 1 ppmV owing to the use of chilled methanol cleaning process. Furthermore, long-term operation of a fully integrated BTL system was successfully conducted for over 500 h. The results showed that the BTL diesel can be used as an alternative automotive diesel fuel.